2016
DOI: 10.4103/0022-3859.180551
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparative clinical study of peripheral blood counts and indices in patients with primary brain tumors

Abstract: Background:Elevation of the neutrophil to lymphocyte ratio (NLR) has been shown to be an indicator of poor prognosis in many malignancies including recurrent glioblastoma multiforme.Objectives:This study was aimed at assessing if the NLR and other leukocyte counts and indices were deranged in treatment-naïve patients with primary brain tumors when compared with an age-matched healthy control group.Materials and Methods:This was a prospective comparative clinical observational study by design. A healthy control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…As corticosteroids consumption increase neutrophil and decrease lymphocyte counts, it may heavily influence NLR. A recent change or tapering schedule in steroid dosage administration was previously related with significant white blood cells variations [21] . In the context of brain tumors, CD4 lymphopenia was associated with worse prognosis [10] .…”
Section: Discussionmentioning
confidence: 99%
“…As corticosteroids consumption increase neutrophil and decrease lymphocyte counts, it may heavily influence NLR. A recent change or tapering schedule in steroid dosage administration was previously related with significant white blood cells variations [21] . In the context of brain tumors, CD4 lymphopenia was associated with worse prognosis [10] .…”
Section: Discussionmentioning
confidence: 99%
“…For a variety of tumours peripheral blood measurement of neutrophils, monocytes or the NLCR can provide correlation with prognosis or predict response to treatment [ 7 , 12 , 15 ]. Recent publications have suggested that a systemic response can even be measured when tumours are confined to immune-privileged sites such as the brain and can be correlated with the presence of malignant histological types and prognosis [ 5 , 17 , 19 ]. It would therefore follow that measurement of the systemic immune response should provide similar insights regarding paediatric intracranial tumours, albeit with a different spectrum of histological subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood counts in patients with brain tumours are not normal when compared to healthy controls [ 17 ]. This is unusual, as the brain is traditionally considered an immune-privileged site and central nervous system inflammation/infection can often manifest with little systemically measurable response [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Among the various inflammatory markers, neutrophil-to-lymphocyte ratio (NLR) is one of the readily available markers and has been proved to be a prognostic marker to predict the survival in high-grade glioma and metastases. 9 10 11 12 13 14 15 16 17 18 19 20 21…”
Section: Introductionmentioning
confidence: 99%